Mitochondrial DNA metabolism in early development of zebrafish (Danio rerio) - Artuso, L.; Romano, A.; Verri, T.; Domenichini, Alice; Argenton, F.; Santorelli, F.; Petruzzella, V. (Elsevier, 2012)
Changes in the mitochondrial DNA (mtDNA) population, together with the expression of a set of genes involved in mtDNA replication and transcription and genes encoding for components of OxPhos complexes, were studied during zebrafish development from early embryo to larval stages. The mtDNA copy number, measured from 1 h post-fertilization to the adult stage, significantly decreased over time, suggesting that mtDNA replication is not active in early zebrafish embryos and that, as in mammals, there occurs partition of the maternal mtDNA copies. Zebrafish genes involved in mtDNA replication (i.e. catalytic subunit of the mtDNA polymerase ?, mitochondrial deoxyribonucleoside kinase) are expressed late in embryo development, further supporting the notion that there is no replication of mtDNA in the early stages of zebrafish development. Notably, as from 4 days post-fertilization, marked expression of replication genes was observed in the exocrine pancreas. Interestingly, the mtDNA helicase, also involved in mtDNA replication, was detected early in development, suggesting diverse regulation of this gene. On the other hand, zebrafish mtDNA transcription genes (i.e. mtDNA-directed RNA polymerase, mitochondrial transcription factor A) were ubiquitously expressed in the early stages of development, suggesting that mitochondrial transcription is already active before mtDNA replication. This hypothesis of early activation of mtDNA transcription fits in with the high early expression of structural OxPhos genes, suggesting that an active OxPhos system is necessary during early embryogenesis. As well as providing the first description of mtDNA distribution during zebrafish development, the present study also represents a step toward the use of Danio rerio as a model for investigation of mitochondrial metabolism and disease. © 2012 Elsevier B.V.